The effect of swimming training and exposure to nicotine derived nitrosamine ketone (NNK) on the immunohistochemical response of tumor-associated macrophages in wistar rats - Ali Barzegari; Shadmehr Mirdar; Mohammad Ranaei (Shahid Beheshti University, 2019)
Purpose: The nicotine derived nitrosamine ketone (NNK) is one of the strongest carcinogens in tobacco that involved in induction of lung cancer by changing the stimulation of tumor associated macrophages. The aim of this study was to effect of swimming training and exposure to nicotine derived nitrosamine ketone (NNK) on the immunohistochemical response of tumor-associated macrophages in wistar rats.Methods: For this purpose, 46 Wistar rats were randomly divided into five groups consist of training, training + NNK, NNK, saline and control. NNK-induced groups received NNK subcutaneously one day per week at a rate of 12/5 mg per kg body weight and the training groups performed submaximal swimming training for 12 weeks. Levels of CD68-Tumor associated macrophages in homogenized lung tissue were measured by immunohistochemistry. To analyze the data; ANOVA and tukey's test were used at a significance level of p≤0.05.Results: The results showed that immunohistochemical expression of TAM in the training group was significantly lower than the NNK group (P = 0.001) (92%). Immunohistochemical expression of TAM was also significantly lower in the NNK + training group than in the NNK group (P = 0.001) (92%). In addition, the immunohistochemical expression of TAM in the NNK group was significantly higher than the solvent group (P = 0.001) (766%).Conclusion: Generally, it could be confirmed that regular submaximal swimming training plays an important role in inhibition of the effects of lung inflammation induced by NNK via decreased of Tumor associated macrophages activity.